THE ROLE AND IMPORTANCE OF THE PRINCIPLE OF LEGAL ACCURACY IN THE SYSTEM OF PRINCIPLES OF LAW - Yusupov Ilkhomjon Ibodillaevich (Scholar Express Journals, 2024)
This article will focus on the principles of law and the specific aspects of the principle of legal accuracy. The principle of legal certainty was analyzed using examples of the fact that it is a real necessity for all areas of legal regulation. The opinions and information of legal scholars and the author on the principle of legal accuracy were given. Some aspects of the application of the principle of legal accuracy are also considered
Keywords: Principles of law; principle of legal accuracy; legality; equality of citizens before the law